1986
DOI: 10.1002/jlac.198619861012
|View full text |Cite
|
Sign up to set email alerts
|

Oxidationen an Thiourethanen, 10. α‐Carbamoylsulfoxide und ‐sulfone, 2. Thiosulfonatbildung bei der Hydrolyse cyclischer α‐Carbamoylsulfoxide

Abstract: Bei der Hydrolyse cyclischer ci-Carbamoylsulfoxide des Thiazintyps 1 und des Thiazolidintyps 4 werden Thiosulfonsaureester des Typs 12 bzw. 14 erhalten, deren neuartige Strukturen durch Spektren und unabhangige Synthesen belegt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…This suggested that two of the three new oxygen atoms are at the S and the last is assigned as the hydroxyl group at N. Further evidence for this was the disappearance of the H−N at δ 6.1. In addition, the amide IR resonance in 2 is absent in 3 , and a new resonance at 1756 cm -1 appeared, indicating the presence of a CONOH system . The OH band at 3448 cm -1 is significantly increased in intensity for 3 , indicating the presence of two OH groups in 3 versus one OH group in 2 .…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…This suggested that two of the three new oxygen atoms are at the S and the last is assigned as the hydroxyl group at N. Further evidence for this was the disappearance of the H−N at δ 6.1. In addition, the amide IR resonance in 2 is absent in 3 , and a new resonance at 1756 cm -1 appeared, indicating the presence of a CONOH system . The OH band at 3448 cm -1 is significantly increased in intensity for 3 , indicating the presence of two OH groups in 3 versus one OH group in 2 .…”
mentioning
confidence: 94%
“…In addition the amide IR resonance in 2 is absent in 3 and a new resonance at 1756 cm −1 appeared, indicating the presence of a CONOH system. 11 The OH band at 3448 cm −1 is significantly increased in intensity for 3 indicating the presence of two OH groups in 3 versus one OH group in 2. The IR showed a strong band at 1051 cm −1 indicating the presence of an SO 2 moiety.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…CrO 3 ) oder durch die schwierige Entsorgung (Chromate, Schwermetalle). Zudem geht die Oxidation oftmals über das gewünschte Produkt II hinaus bis zur Stufe der Thiolurethan-Soxide III oder -S,S-dioxide IV [21], die durch leicht erfolgende Hydrolysereaktionen das Produktgemisch noch heterogener machen [22].…”
unclassified